THE ROLE OF LITERATURE IN SHAPING THE CHARACTER OF LEARNER - Wardiah, Dessy (Jurnal Dosen Universitas PGRI Palembang)
AbstractIn Indonesia, the education of literature is sometimes ignored and neglected. Since new era of paradigm, literature is treated as non significant subject of learning, it is considered to be unimportant, useless, and all sorts of no other forms. Education in Indonesia only focuses on meaningful learning of science and mathematics. Although it is not expressed verbally, literature is viewed lower than science and mathematics. The willingness to keep forward science is failed, because of ignoring literary education. In line with the growing magnitude of the need for character education now, literary education and learning needs were designed. Literature is treated as a basic character education. In such context, there should be serious efforts of all components of the nation to build a "collective consciousness" in order to restore lost national character. In such context, it becomes interesting when as an educator of language and literature to give or to inject values into a insightful character education lessons which were labeled asÂ  literature and sought to encourage and to internalize the character education through literature.Â Keywords:Character Education, Literature Learning